INDONESIA'S ROLE IN THE NUCLEAR NON-PROLIFERATION TREATY (NPT) - Sitti Nurtina (Universitas Bina Mandiri Gorontalo, 2025)
This paper is a study of Indonesia in the nuclear non-proliferation treaty (NPT) where the focus of the discussion is on the analysis of the background of Indonesia ratifying the Nuclear Non-Proliferation (NPT) regime and outlining Indonesia's policies related to support for the nuclear non- proliferation regime. This paper will explain and analyze how Indonesia's role and position are in supporting the Nuclear Non-Proliferation (NPT) and what its implications are. Can it maintain or improve Indonesia's position in International Relations and most importantly its effects on international peace and security.